High uric acid induced hippocampal mitochondrial dysfunction and cognitive impairment involving intramitochondrial NF-κB inhibitor α/nuclear factor-κB pathway. Issue 3 (1st February 2022) - Shi, Chun; Guo, Han; Liu, Xintong
Abstract : Objectives: Epidemiological research has indicated that hyperuricemia may impair cognitive ability; however, the underlying mechanisms remain unclear. The present study thus investigated the possible mechanism underlying hyperuricemia-related cognitive impairment. Methods: Using hyperuricemic rats and high uric acid (UA) intracerebroventricularly treated mice, the current study elucidated whether and how high UA impaired cognitive ability and hippocampal mitochondrial bioenergetic function. Results: Hyperuricemia induced UA uptake by hippocampal mitochondria, which impaired cognitive ability and disrupted the bioenergetic function of hippocampal mitochondria, indicated by reduced ATP production and decreased cytochrome c oxidase (COX) activity. Mechanistically, excess UA might trigger intramitochondrial NF-κB inhibitor α (IκBα)/nuclear factor-κB (NF-κB) pathway to downregulate the subunit III of COX (COXIII). Conclusion: The results provided new insights into the mechanism underlying hyperuricemia-related cognitive decline.